Road Traffic and Aircraft Noise as Drivers of Environmental Protest? - Peter Preisendörfer; Lucie Herold; Karin Kurz (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
This article investigates whether and to what extent unfavorable local environmental conditions furnish an important motivator for environmental protest. We do so using individual-level data on objective and subjectively perceived residential road traffic and aircraft noise pollution, pertaining to the cities of Mainz (Germany) and Zurich (Switzerland). By referring to fine-grained noise data, we are able to test the predictive power of grievances and self-interest in explaining protest participation more stringently than has been the case in most previous studies. Theoretically, our study is inspired by Klandermans' socio-psychological framework of political protest, the pressure-response approach, the self-interest perspective, and the collective-interest model. Our empirical findings only partially confirm the grievances assumption that unfavorable local environmental conditions in the form of residential road traffic and aircraft noise stimulate environmental protest. Noise caused by airplanes seems to be more “protest-inducing” than that produced by road traffic. It is not so much the objectively measurable noise level as its subjective perception and evaluation that are deciding factors. However, in line with Klandermans' protest framework and other theories of political protest, there are more influential drivers of environmental protest, such as environmental concerns and a~left-wing political ideology. Thus, the effects of residential road traffic and aircraft noise turn out to be relatively moderate. Ultimately, this means that our tailored measures of grievances corroborate a~relatively well-established finding of protest research.
Keywords: 300; Noise pollution; Environmental risks; Environmental activism; Political protest; Theories of political protest; Lärmbelastung; Umweltrisiken; Umweltaktivismus; Politischer Protest; Theorien politischen Protests